Hydrocarbon steam reforming catalyst and preparation method thereof

By using potassium feldspar, sepiolite composite support and multi-layer structure-distributed active components, a high-activity and high carbon deposit resistance catalyst that can be activated without external hydrogen supply was prepared, which solved the problem of insufficient activity of existing catalysts in modular hydrogen production equipment and the need for external hydrogen supply, and achieved self-reduction and activation and efficient application of the catalyst.

CN119909703AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311420247.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02
Estimated Expiration
2043-10-30

Smart Images

  • Figure CN119909703A_ABST
    Figure CN119909703A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrocarbon steam reforming catalyst and a preparation method thereof, and the method comprises the following steps: (1) taking a certain amount of potassium feldspar and sepiolite in a potassium hydroxide aqueous solution, soaking for a certain time at a certain temperature, settling, removing impurities, and carrying out first drying to obtain a substance a; (2) mixing and molding the substance a and a carrier auxiliary agent to obtain a carrier b; (3) dissolving lanthanum salt or cerium salt and cobalt salt, adding a certain amount of nickel salt to prepare steeping liquor c, placing the carrier b in the steeping liquor c for a certain time, and performing secondary drying and primary roasting to obtain a mixture d; and (4) taking a certain amount of ruthenium salt to prepare an impregnation liquid e, placing the mixture d in the impregnation liquid e for a certain time, and carrying out third drying and second roasting to obtain the catalyst. The hydrocarbon steam catalyst does not need to be activated by external hydrogen, can be self-reduced, and has high activity and high carbon deposition resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a novel hydrocarbon steam reforming catalyst suitable for a hydrogen production device and a preparation method thereof. Background Art

[0002] As a green and clean energy, hydrogen energy has become an important part of the national energy strategy. The production and effective utilization of hydrogen energy is the research focus and hotspot of colleges and universities and social research institutions. In order to cater to the coming hydrogen energy era, it is urgent to develop modular hydrogen production equipment and its supporting catalysts. For modular hydrocarbon steam reforming hydrogen production equipment, due to its highly integrated reactor and more stringent process conditions, the process conditions and activity of existing industrial catalysts cannot meet the use requirements. Therefore, it is necessary to develop high-activity converters suitable for modular hydrogen production. The process flow and process parameters of modular hydrogen production equipment are significantly different from those of traditional factory hydrogen production equipment. It is not a simple miniaturization of the existing mature industrial hydrocarbon hydrogen production. The catalysts used, process flow, reactors, heat balance and other aspects need to be broken through and innovated. Modular devices are easy to assemble and apply, but they also face the limitation that commonly used materials are not convenient to supply. Improving the applicability of catalysts and eliminating the catalyst pretreatment activation process are more conducive to the promotion and application of devices. There are two types of commonly used hydrocarbon conversion catalysts, namely precious metal and non-precious metal. Precious metal catalysts, ruthenium series, generally have high catalytic activity and good anti-coking performance, but are expensive. Non-precious metal catalysts, nickel-based series, although they have excellent catalytic activity and low price, have the disadvantages of easy coking and sintering deactivation. How to overcome the shortcomings of various catalysts and take their advantages to apply in modular devices is the focus of research and development. In order to adapt to the limitations of various raw materials and modular devices, it is urgent to develop highly active, self-reducible, and highly carbon-resistant conversion catalysts.

[0003] The invention patent application of Chinese patent publication number CN115739065A discloses a novel hydrocarbon steam reforming catalyst and a preparation method thereof, comprising: (1) taking a certain amount of nickel source and dissolving it in water to obtain solution A; (2) taking a certain amount of montmorillonite and hydrotalcite and soaking them in water, settling, removing impurities and drying them respectively, and then mixing the dried montmorillonite and hydrotalcite to obtain mixture B; (3) adding a potassium source to mixture B and mixing them thoroughly, and grinding them for a certain period of time to obtain mixture C; (4) transferring mixture C to a crystallization kettle, crystallizing at 175-215° C. for 12-48 hours, taking out, adding a lubricant, granulating, and extruding to obtain mixture D; (5) adding mixture D to solution A obtained in step (1) and soaking it for a certain period of time, taking out, drying, and calcining to obtain a catalyst; wherein, in step (3), the potassium source comprises a first potassium source and a second potassium source, wherein the first potassium source is selected from at least one of potassium aluminate and potassium metaaluminate, and the second potassium source is selected from at least one of potassium hydroxide and potassium carbonate. The invention uses nickel as the active component, homemade potassium pyroxene as the anti-carbon agent, and montmorillonite-hydrotalcite as the carrier to prepare the catalyst. The obtained catalyst needs to be reduced in a hydrogen atmosphere to be active and is not suitable for situations where there is no external hydrogen supply. Summary of the invention

[0004] Based on the problems of the prior art, the present invention provides a hydrocarbon steam reforming catalyst and a preparation method thereof. The catalyst does not require external hydrogen supply for activation, can be self-reduced, and has high activity and high resistance to carbon deposition.

[0005] The technical solution provided by the present invention is as follows: A first aspect of the present invention provides a method for preparing a hydrocarbon steam reforming catalyst, comprising: (1) taking a certain amount of potassium feldspar and sepiolite in a potassium hydroxide aqueous solution, soaking them at a certain temperature for a certain period of time, settling them, removing impurities, and performing a first drying to obtain substance a; (2) mixing the substance a and a carrier auxiliary agent to obtain a carrier b; (3) dissolving lanthanum salt or cerium salt, cobalt salt, and adding a certain amount of nickel salt to prepare an impregnation solution c, placing the carrier b in the impregnation solution c for a certain period of time, and then performing a second drying and a first calcination to obtain a mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C×ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion or cerium ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; the numerical range of C is 0.3-5; the numerical range of ґ is 2.2-7; the numerical range of Ԑ is 1.6-2.2; the numerical range of A is 0.3-20; (4) A certain amount of ruthenium salt is prepared into an impregnation solution e, and the mixture d is placed in the impregnation solution e for a certain period of time, followed by a third drying and a second calcination to obtain a catalyst.

[0006] Preferably, in step (1), the mass ratio of potassium feldspar to sepiolite is 1:4-1:8.

[0007] Preferably, in step (1), the soaking time is 180-360 min. More preferably, the soaking time is 200-300 min.

[0008] Preferably, in step (1), the soaking temperature is 200-250°C.

[0009] Preferably, in step (2), the carrier auxiliary agent is at least one of polyethylene glycol, starch, and sucrose. More preferably, the carrier auxiliary agent is polyethylene glycol.

[0010] Preferably, in step (2), the adhesive lubricant is nitric acid and / or citric acid.

[0011] Preferably, in step (3), the nickel salt is at least one of nickel nitrate, nickel acetate and nickel oxalate, and the lanthanum salt or cerium salt is a soluble salt.

[0012] More preferably, in step (3), the nickel salt is nickel nitrate, and the lanthanum salt or cerium salt is nitrate.

[0013] Preferably, in step (3), the mass ratio of the lanthanum salt or cerium salt: the cobalt salt: the nickel salt is 1:0.67:1-1:1.2:1.2.

[0014] Preferably, in step (3), the first roasting is to heat the semi-finished product obtained by the second drying to 180-250°C at a rate of 1-4°C / min, roast it at a constant temperature for 1-2 hours, and then heat it to 350-450°C at a rate of 1-4°C / min and roast it at a constant temperature for 2-3 hours; in step (4), the second roasting is to heat the semi-finished product obtained by the third drying to 180-200°C at a rate of 1-4°C / min, roast it at a constant temperature for 1-2 hours, and then heat it to 400-550°C at a rate of 1-4°C / min and roast it at a constant temperature for 2-3 hours.

[0015] Preferably, in step (4), the ruthenium salt is a water-soluble salt. More preferably, the ruthenium salt is ruthenium chloride.

[0016] The second aspect of the present invention provides a hydrocarbon steam reforming catalyst obtained by the above-mentioned preparation method, wherein the active components of the catalyst are distributed in multiple layers along the radial direction of the carrier, the active component of the outermost layer of the core is ruthenium, the catalyst promoter is lanthanum oxide or cerium oxide, the active components of the middle layer of the shell are nickel oxide and cobalt oxide, and the core is nickel oxide; wherein ruthenium accounts for 0.02-0.2% of the mass of the catalyst, lanthanum oxide or cerium oxide accounts for 0.5-1.5% of the mass of the catalyst, nickel oxide accounts for 5.5-8.5% of the mass of the catalyst, cobalt oxide accounts for 1-3.8% of the mass of the catalyst, and the remaining components of the catalyst are composite carriers.

[0017] The beneficial effects of the present invention include at least: The active metal components in the hydrocarbon steam reforming catalyst of the present invention are distributed in multiple layers along the radial direction of the carrier. The active component of the outermost layer of the core is ruthenium, and the active metal components of the middle layer of the shell are nickel oxide and cobalt oxide. The core is nickel oxide, which presents a multi-layer structure. The outermost layer of the core provides the initial activity of the catalyst to promote the conversion reaction. At the same time, the generated hydrogen gradually diffuses into the interior of the catalyst to reduce the oxidized metal, thereby improving the catalyst activity so that the modular hydrogen production device conversion catalyst can be gradually self-reduced and activated without external hydrogen supply, so as to achieve the purpose of environmental protection and energy saving, and meet the use requirements of the modular hydrogen production device conversion catalyst.

[0018] In the kalcysite-sepiolite composite carrier of the hydrocarbon steam reforming catalyst of the present invention, the active center of the sepiolite converts the adsorbed organic matter into an activated complex, and the kalcysite enters the sepiolite fiber rod layer structure to stabilize the catalyst structure. At the same time, the flowing gaseous potassium alkali provides alkalinity to promote the reaction of carbon with water vapor and reduce carbon deposition. The catalyst has high resistance to carbon deposition.

[0019] When the hydrocarbon steam reforming catalyst prepared by the present invention is used in industry, the reforming catalyst of the modular device can be activated by self-reduction without external hydrogen, can be self-reduced, has high activity and high resistance to carbon deposition, and has good economic benefits and application prospects.

[0020] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a small pressurized evaluation device used in the test of the present invention.

[0022] Figure 2 It is a graph of unloaded sample carbon content obtained from the performance test of hydrocarbon steam reforming catalysts of the embodiments of the present invention and the comparative examples.

[0023] Description of Reference Numerals exist Figure 1Among them, 1. oil metering pump, 2. water metering pump, 3. vaporizer, 4. mixer, 5. tubular reactor, 6. condenser, 7. separator, 8. regulator, 9. wet flow meter. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and beneficial effects of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. Examples of the embodiments are shown in the accompanying drawings. It should be understood that the specific embodiments described in the following embodiments of the present invention are only exemplary descriptions of the specific embodiments of the present invention, and are intended to be used to explain the present invention, but do not constitute a limitation of the present invention.

[0025] The endpoints of the scope disclosed in this article and any value are not limited to this accurate scope or value, and these scopes or values ​​should be understood as comprising values ​​close to these scopes or values.For numerical range, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article.In the description of the application, unless otherwise stated, the meaning of similar words such as "one / a kind", "multiple / multiple" is two / kinds or more than two / kinds.

[0026] A first aspect of the present invention provides a method for preparing a hydrocarbon steam reforming catalyst, comprising: (1) taking a certain amount of potassium feldspar and sepiolite in a potassium hydroxide aqueous solution, soaking them at a certain temperature for a certain period of time, settling them, removing impurities, and performing a first drying to obtain substance a; (2) mixing the substance a and a carrier auxiliary agent to obtain a carrier b; (3) dissolving lanthanum salt or cerium salt, cobalt salt, and adding a certain amount of nickel salt to prepare an impregnation solution c, placing the carrier b in the impregnation solution c for a certain period of time, and then performing a second drying and a first calcination to obtain a mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C×ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion or cerium ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; the numerical range of C is 0.3-5; the numerical range of ґ is 2.2-7; the numerical range of Ԑ is 1.6-2.2; the numerical range of A is 0.3-20; (4) A certain amount of ruthenium salt is prepared into an impregnation solution e, and the mixture d is placed in the impregnation solution e for a certain period of time, followed by a third drying and a second calcination to obtain a catalyst.

[0027] Sepiolite is a magnesium-rich silicate clay mineral with a theoretical chemical formula of Mg 8 [Si12 O 30 ](OH) 4 12H 2 O, 4 of the water molecules are crystal water, and the rest are zeolite water. Sepiolite belongs to the chain-layered hydrous magnesium aluminum silicate or magnesium silicate mineral of S monoclinic system or orthorhombic system. It has a huge specific surface area and can adsorb various reactants and active components of catalysts. Since sepiolite has alkaline and acidic centers, reactants are easily polarized into activated complexes at the center, which produce synergistic catalytic effects with catalysts. Sepiolite has a fibrous structure, which can form a large specific surface and interparticle gaps, has strong adsorption, and can provide more active points, but the mechanical strength of sepiolite is poor. It is not strong enough to be used as a catalyst carrier alone, and other carriers need to be added for use together.

[0028] Potassium feldspar is used as a raw material, and kalcylindrical is produced through the reaction process of the present invention. In the finished catalyst, a composite carrier structure of kalcylindrical-sepiolite is present. In the composite carrier structure of kalcylindrical-sepiolite of the present invention, the active center of sepiolite converts adsorbed organic matter into an activated complex, and the produced kalcylindrical enters the sepiolite fiber layer structure, so that the catalyst structure is stable and potassium is not easily lost at high temperature. At the same time, the flowing gaseous potassium alkali provides alkalinity, promotes the reaction of carbon with water vapor, reduces carbon deposition, and the catalyst has high resistance to carbon deposition.

[0029] The composite carrier structure of pyroxene-sepiolite of the present application not only has the advantages of high potassium content and potassium in the lattice is not easily lost at high temperature, but also can play a good role in resisting carbon deposition as a catalyst or catalyst promoter in hydrogen production conversion catalyst.

[0030] According to the present invention, the amount of potassium feldspar and sepiolite is 1:2-1:10. In some preferred embodiments, in step (1), the mass ratio of potassium feldspar to sepiolite is 1:4-1:8.

[0031] According to the present invention, in step (1), the concentration of the potassium hydroxide aqueous solution is 10-60wt%. In some preferred embodiments, in step (1), the concentration of the potassium hydroxide aqueous solution is 20-45wt%. According to the present invention, in step (1), the soaking temperature is generally 210-260° C. In some preferred embodiments, in step (1), the soaking temperature is 220-250° C.

[0032] According to the present invention, in step (1), the soaking time is generally 180-360 min. In some preferred embodiments, in step (1), the soaking time is 200-300 min.

[0033] According to the present invention, in step (1), the drying temperature of the first drying is 80-150° C., preferably 90-110° C.; the drying time is 240-600 min, preferably 360-550 min.

[0034] According to the present invention, in step (2), the carrier auxiliary agent is an organic carrier auxiliary agent. In some preferred embodiments of the present invention, in step (2), the carrier auxiliary agent is at least one of polyethylene glycol, starch, and sucrose. More preferably, the carrier auxiliary agent is polyethylene glycol.

[0035] According to the present invention, in step (2), the amount of the carrier auxiliary agent used accounts for 1%-4% of the mass of substance a. In some preferred embodiments, in step (2), the amount of the carrier auxiliary agent used accounts for 2%-3.5% of the mass of substance a.

[0036] According to the present invention, the raw material of carrier b also includes a binding lubricant, which has no negative impact on the catalyst preparation process and catalyst performance, and can promote the formation of the above-mentioned composite carrier structure of the present invention. The inorganic acid and / or organic acid, such as at least one of nitric acid, citric acid, acetic acid, and oxalic acid. In a preferred embodiment, in step (2), the binding lubricant is nitric acid and / or citric acid.

[0037] According to the present invention, in step (2), the amount of the adhesive lubricant used is 1%-4% of the mass of substance a. In some preferred embodiments, in step (2), the amount of the adhesive lubricant used is 2%-3.5% of the mass of substance a.

[0038] According to the present invention, a solvent is also added during the molding process of the carrier b, which can be selected from the molding solvent. In some preferred embodiments, the solvent is water.

[0039] According to the present invention, during the molding of carrier b, the amount of solvent used accounts for 50%-70% of the mass of substance a. In some preferred embodiments, the amount of solvent used accounts for 50%-65% of the mass of substance a.

[0040] According to the present invention, in step (3), the lanthanum salt or cerium salt is a soluble salt. In some preferred embodiments, the lanthanum salt or cerium salt is a nitrate.

[0041] According to the present invention, in step (3), the cobalt salt is a soluble salt. In some preferred embodiments, the cobalt salt is a nitrate.

[0042] According to the present invention, in step (3), the nickel salt is at least one of nickel nitrate, nickel acetate, and nickel oxalate. In some preferred embodiments, in step (3), the nickel salt is nickel nitrate.

[0043] According to the present invention, in step (3), the mass ratio of the lanthanum salt or cerium salt: cobalt salt: nickel salt is 1:0.5:1-1:1.5:1.5. In some preferred embodiments, in step (3), the mass ratio of the lanthanum salt or cerium salt: cobalt salt: nickel salt is 1:0.67:1-1:1.2:1.2.

[0044] According to the present invention, in step (3), the solvent for preparing the impregnation liquid c is at least one of water, alcohol, and dilute acid. In some preferred embodiments, in step (3), the solvent for preparing the impregnation liquid c is water.

[0045] According to the present invention, in step (3), an equal volume impregnation method is adopted.

[0046] According to the present invention, in step (3), the carrier b is placed in the impregnation liquid c for 1-3 hours. In some preferred embodiments, in step (3), the carrier b is placed in the impregnation liquid c for 1.5-2 hours.

[0047] According to the present invention, in step (3), the drying temperature of the second drying is 80-130° C., preferably 95-110° C.; the drying time is 300-500 min, preferably 350-450 min.

[0048] According to the present invention, in step (3), the first roasting method is to heat the second dried semi-finished product to 170-280°C at a rate of 1-5°C / min, roast it at a constant temperature for 1-3h, and then heat it to 350-450°C at a rate of 1-5°C / min and roast it at a constant temperature for 1-3h.

[0049] According to the present invention, in step (4), the mixture d is placed in the immersion liquid e for 200-400 minutes. In some preferred embodiments, in step (4), the mixture d is placed in the immersion liquid e for 250-300 minutes.

[0050] According to the present invention, in step (4), the drying temperature of the third drying is 70-120° C., preferably 75-95° C.; the drying time is 350-550 min, preferably 400-500 min.

[0051] According to the present invention, in step (4), the second roasting method is to heat the third dried semi-finished product to 160-210°C at a rate of 1-5°C / min, roast it at a constant temperature for 1-3h, and then heat it to 380-580°C at a rate of 1-5°C / min and roast it at a constant temperature for 1-3h.

[0052] According to the present invention, in some preferred embodiments, in step (3), the first roasting is to heat the second dried semi-finished product to 180-250°C at a rate of 1-4°C / min, roast at a constant temperature for 1-2h, and then heat it to 350-450°C at a rate of 1-4°C / min and roast at a constant temperature for 2-3h; in step (4), the second roasting is to heat the third dried semi-finished product to 180-200°C at a rate of 1-4°C / min, roast at a constant temperature for 1-2h, and then heat it to 400-550°C at a rate of 1-4°C / min and roast at a constant temperature for 2-3h.

[0053] According to the present invention, in step (4), the ruthenium salt is a water-soluble salt. In some preferred embodiments, the ruthenium salt is ruthenium chloride.

[0054] According to the present invention, in step (4), an equal volume impregnation method is adopted.

[0055] According to the present invention, in step (4), the shape of the catalyst can be set as required. In some preferred embodiments, the catalyst is in the shape of a cylindrical cylinder with a diameter of 7×7 mm, a middle ring with a diameter of 1 mm, and a wall thickness of 3 mm.

[0056] The second aspect of the present invention provides a hydrocarbon steam reforming catalyst prepared by the above-mentioned preparation method, which has ruthenium, nickel and cobalt as active components and potassium pyroxene-sepiolite as a composite carrier; the active metal components of the catalyst prepared by the present invention are distributed in multiple layers along the radial direction of the carrier, the active component of the outermost layer of the core is ruthenium, the catalyst promoter is lanthanum oxide or cerium oxide, the active metal components of the middle layer of the shell are nickel oxide and cobalt oxide, and the core is nickel oxide, which has a multi-layer structure. The outermost layer of the core provides the initial activity of the catalyst to promote the initial conversion reaction. At the same time, the hydrogen generated gradually diffuses into the interior of the catalyst to reduce the oxidized metal, thereby improving the catalyst activity so that the modular hydrogen production device conversion catalyst can be gradually reduced in the self-produced hydrogen, so as to achieve the purpose of environmental protection and energy saving, and meet the use requirements of the modular hydrogen production device conversion agent.

[0057] The conversion catalyst of the present invention contains 7.02-14% (m / m) of active components, the outermost layer thickness of the catalyst core is 0.5-1mm, the shell middle layer thickness is 0.5-1mm, and the core layer thickness is 1-2mm.

[0058] The active components are distributed in layers of ruthenium, cobalt oxide and nickel oxide (i.e., the outermost active component of the core is ruthenium, the catalyst promoter is lanthanum oxide or cerium oxide, the active components of the shell middle layer are nickel oxide and cobalt oxide, and the core is nickel oxide), wherein the ruthenium content accounts for 0.02-0.2% of the catalyst mass, the lanthanum oxide or cerium oxide accounts for 0.5-1.5% of the catalyst mass, the nickel oxide accounts for 5.5-8.5% of the catalyst mass, the cobalt oxide content accounts for 1-3.8% of the catalyst mass, and the remaining components of the catalyst are composite carriers. The prepared impregnation solution satisfies the relationship C=C1 / C2, A=C×ґ / Ԑ (the numerical range of C is 0.3-5, the numerical range of ґ is 2.2-7, the numerical range of Ԑ is 1.6-2.2, and the numerical range of A is 0.3-20). Under this condition, the carrier is impregnated with an active component impregnation solution of appropriate concentration to effectively form a multi-layer active component distribution.

[0059] The pore volume of the catalyst carrier prepared by the present invention is controlled at ≥0.35 mL / g, the side pressure crushing strength is ≥300 N / cm, the raw materials are light hydrocarbons such as natural gas, synthesis gas, and refinery gas, and the particle size of the active component nickel and cobalt is less than or equal to 12 nm.

[0060] The hydrocarbon steam reforming catalyst prepared by the present invention is suitable for a reforming furnace inlet temperature of 450-650°C, an outlet temperature of 750-880°C, and a reforming carbon space velocity of 10000h -1 ; Total water-carbon ratio 2.0-3.5; Hydrogen production process conditions of pressure 2.0-4.0 MPa. It is worth noting that the application scenario of the present invention is not limited to this.

[0061] The hydrocarbon steam reforming catalyst prepared by the present invention can realize the self-reduction activation of the reforming catalyst in a modular device without external hydrogen when used in industry, can be self-reducible, has high activity and high resistance to carbon deposition, and has good economic benefits and broad application prospects.

[0062] Unless otherwise specified, the raw materials used in the examples and comparative examples are commercially available.

[0063] Example 1. Preparation of hydrocarbon steam reforming catalyst (1) 20.9 g of potassium feldspar and 62.8 g of sepiolite were soaked in a 40 wt% aqueous solution containing 16.9 g of potassium hydroxide at 220°C for 200 min, allowed to settle, impurities removed, and dried at 90°C for 420 min to obtain substance a; (2) Substance a is mixed with 3 g of polyethylene glycol, 3 g of nitric acid, and 56 g of water to obtain carrier b; (3) Dissolve lanthanum nitrate and cobalt nitrate, add 38.3 g of nickel nitrate and 55 g of water to obtain impregnation solution c, place b in c for 1.5 hours, dry at 95°C for 400 min, heat to 250°C at a rate of 3°C / min, calcine at constant temperature for 2 h, then heat to 450°C at a rate of 3°C / min and calcine at constant temperature for 3 h to obtain mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C×ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; wherein the values ​​of C, A, ґ, and Ԑ are shown in Table 1; (4) Take 0.97 g of ruthenium chloride and prepare impregnation solution e by equal volume impregnation method. Place d in e for 300 min, dry at 85°C for 500 min, heat to 180°C at a rate of 3°C / min, calcine at constant temperature for 2 h, and then heat to 550°C at a rate of 3°C / min and calcine at constant temperature for 2.5 h to obtain a hydrocarbon steam reforming catalyst.

[0064] Example 2: Preparation of hydrocarbon steam reforming catalyst (1) 23.1 g of potassium feldspar and 69.3 g of sepiolite were soaked in an aqueous solution containing 18.6 g of potassium hydroxide at a concentration of 35 wt%, at 250 ° C for 300 min, allowed to settle, impurities removed, and dried at 100 ° C for 360 min to obtain substance a; (2) Substance a is mixed with 3 g of polyethylene glycol, 3 g of nitric acid, and 60 g of water to obtain carrier b; (3) Dissolve lanthanum nitrate and cobalt nitrate, add 22.9 g of nickel nitrate and 50 g of water to obtain impregnation solution c, place b in c for 2 hours, dry at 95°C for 450 min, heat to 200°C at a rate of 2°C / min, calcine at constant temperature for 2 h, then heat to 400°C at a rate of 2°C / min and calcine at constant temperature for 3 h to obtain mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C*ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; wherein the values ​​of C, A, ґ, and Ԑ are shown in Table 1; (4) Take 0.12 g of ruthenium chloride prepared as impregnation solution e by equal volume impregnation method, place d in e for 280 min, dry at 95°C for 350 min, heat to 200°C at a rate of 2°C / min, calcine at constant temperature for 1.5 h, then heat to 550°C at a rate of 2°C / min and calcine at constant temperature for 2 h to obtain a hydrocarbon steam reforming catalyst.

[0065] Example 3. Preparation of hydrocarbon steam reforming catalyst (1) 14.7 g of potassium feldspar and 73.4 g of sepiolite were soaked in an aqueous solution containing 11.8 g of potassium hydroxide at a concentration of 20 wt%, at 250 ° C for 250 min, allowed to settle, impurities removed, and dried at 110 ° C for 360 min to obtain substance a; (2) Substance a is mixed with 3 g of polyethylene glycol, 3 g of nitric acid, and 64 g of water to obtain carrier b; (3) Dissolve lanthanum nitrate and cobalt nitrate, add 30.9 g of nickel nitrate and 52 g of water to obtain impregnation solution c, place b in c for 1.5 hours, dry at 110°C for 350 minutes, heat to 250°C at a rate of 4°C / min, calcine at constant temperature for 2 hours, then heat to 400°C at a rate of 3°C / min and calcine at constant temperature for 2.5 hours to obtain mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C×ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; wherein the values ​​of C, A, ґ, and Ԑ are shown in Table 1; (4) Take 1.2 g of ruthenium chloride and prepare impregnation solution e by equal volume impregnation method. Place d in e for 250 min, dry at 75°C for 550 min, heat to 200°C at a rate of 4°C / min, calcine at constant temperature for 2 h, then heat to 550°C at a rate of 3°C / min and calcine at constant temperature for 3 h to obtain hydrocarbon steam reforming catalyst.

[0066] Comparative Example 1: Preparation of hydrocarbon steam reforming catalyst (1) 21.6 g of potassium feldspar and 64.9 g of sepiolite were soaked in a 40 wt% aqueous solution containing 17.4 g of potassium hydroxide at 220°C for 200 min, allowed to settle, impurities removed, and dried at 90°C for 420 min to obtain substance a; (2) Substance a is mixed with 3 g of polyethylene glycol, 3 g of nitric acid, and 58 g of water to obtain carrier b; (3) Dissolve lanthanum nitrate and cobalt nitrate, add 39.6 g of nickel nitrate and 57 g of water to obtain impregnation solution c, place b in c for 1.5 hours, dry at 95°C for 400 min, heat to 250°C at a rate of 3°C / min, calcine at constant temperature for 2 h, then heat to 450°C at a rate of 3°C / min and calcine at constant temperature for 3 h to obtain mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C*ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; wherein the values ​​of C, A, ґ, and Ԑ are shown in Table 1; (4) Take 1.38 g of ruthenium chloride and prepare impregnation solution e by equal volume impregnation method. Place d in e for 250 min, dry at 85°C for 500 min, heat to 180°C at a rate of 3°C / min, calcine at constant temperature for 2 h, then heat to 550°C at a rate of 3°C / min and calcine at constant temperature for 2.5 h to obtain hydrocarbon steam reforming catalyst.

[0067] Comparative Example 2: Preparation of hydrocarbon steam reforming catalyst (1) 83.8 g of sepiolite was soaked in a 40 wt% aqueous solution containing 16.9 g of potassium hydroxide at 220°C for 200 min, allowed to settle, impurities removed, and dried at 90°C for 420 min to obtain substance a; (2) Substance a is mixed with 3 g of polyethylene glycol, 3 g of nitric acid, and 56 g of water to obtain carrier b; (3) Dissolve lanthanum nitrate and cobalt nitrate, add 38.3 g of nickel nitrate and 55 g of water to obtain impregnation solution c, place b in c for 1.5 hours, dry at 95°C for 400 min, heat to 250°C at a rate of 3°C / min, calcine at constant temperature for 2 h, then heat to 450°C at a rate of 3°C / min and calcine at constant temperature for 3 h to obtain mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C×ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; wherein the values ​​of C, A, ґ, and Ԑ are shown in Table 1; (4) Take 0.97 g of ruthenium chloride and prepare impregnation solution e by equal volume impregnation method. Place d in e for 300 min, dry at 85°C for 500 min, heat to 180°C at a rate of 3°C / min, calcine at constant temperature for 2 h, then heat to 550°C at a rate of 3°C / min and calcine at constant temperature for 2.5 h to obtain hydrocarbon steam reforming catalyst.

[0068] Comparative Example 3: Preparation of hydrocarbon steam reforming catalyst (1) 14.5 g of potassium feldspar and 72.4 g of sepiolite were soaked in an aqueous solution containing 11.7 g of potassium hydroxide at a concentration of 20 wt%, at 220 °C for 200 min, allowed to settle, impurities removed, and dried at 90 °C for 420 min to obtain substance a; (2) Substance a is mixed with 3 g of polyethylene glycol, 3 g of nitric acid, and 60 g of water to obtain carrier b; (3) Dissolve lanthanum nitrate and cobalt nitrate, add 37.3 g of nickel nitrate and 57 g of water to obtain impregnation solution c, place b in c for 1.5 hours, dry at 95°C for 400 min, heat to 250°C at a rate of 3°C / min, calcine at constant temperature for 2 h, then heat to 450°C at a rate of 3°C / min and calcine at constant temperature for 3 h to obtain mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C*ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; wherein the values ​​of C, A, ґ, and Ԑ are shown in Table 1; Take 1.38 g of ruthenium chloride and prepare impregnation solution e by equal volume impregnation method. Place d in e for 250 minutes, dry at 85°C for 500 minutes, heat to 180°C at a rate of 3°C / min, calcine at constant temperature for 2 hours, then heat to 550°C at a rate of 3°C / min and calcine at constant temperature for 2.5 hours to obtain a hydrocarbon steam reforming catalyst.

[0069] Table 1 Composition of hydrocarbon steam reforming catalyst .

[0070] Test Example 1: Hydrocarbon Steam Reforming Catalyst Performance Test use Figure 1 The small-scale pressurized evaluation device and evaluation conditions shown are used to test the hydrocarbon steam reforming catalysts prepared in the above examples and comparative examples.

[0071] Specific evaluation conditions include: hydrocarbon feedstock enters the vaporization mixer through a metering pump and is mixed with water vapor into the reactor, and the reformed gas is discharged after chromatographic analysis. The reactor is a tubular reactor with an inner diameter of φ19mm, with four sections of external heating, and the temperature can be adjusted in sections. The first section of heating corresponds to an empty tube, which is mainly used to heat the feedstock, and the second, third, and fourth sections heat the hydrocarbon steam reforming catalyst.

[0072] During the evaluation of hydrocarbon steam reforming catalysts, the reactor external heating section is used as a heat preservation to minimize the heat exchange between the reaction and the outside world. The reactor is equipped with a φ6mm thermocouple tube and four thermocouples, corresponding to the inlet, 1 / 3, 1 / 2 and outlet of the catalyst bed.

[0073] Catalyst: crushed into 10-20 mesh, loaded 45mL, bed height 270mm.

[0074] Using n-hexane as raw material, pressure 3.0MPa, carbon space velocity 10000h -1 , H 2 O / C (mol / mol) 2.0; bed temperature: inlet temperature 480°C, outlet temperature 700°C, operation time: 100h.

[0075] The results are shown in Table 2 below.

[0076] Table 2 Hydrocarbon steam reforming catalyst performance test results .

[0077] It can be seen from Table 2 that the hydrocarbon steam reforming catalyst in the embodiment of the present invention is slowly activated, and the active components of the catalyst are gradually reduced by self-produced hydrogen. It is a self-reduction process, and the catalyst activity gradually increases. The high activity of the catalyst can fully meet the use requirements, the unloading carbon content is low, and it has high resistance to carbon deposition.

[0078] In comparative example 1, the active component ruthenium is higher than the range value, the cobalt is lower than the range value, and the lanthanum is higher than the range value. The particle size of the active component of the obtained catalyst D becomes larger, the hydrogen production becomes less, and the unloading carbon content becomes higher; in comparative example 2, there is only one carrier, sepiolite, the ґ value is higher than the range value, and the Ԑ value is higher than the range value. The particle size of the active component of the obtained catalyst E becomes significantly larger, and the unloading carbon content becomes significantly higher; in comparative example 3, the ruthenium is higher than the range value, the cobalt is lower than the range value, the lanthanum is higher than the range value, the C value is lower than the range value, and the ґ value is higher than the range value. Compared with comparative example 1, the particle size of the active component is larger, and the unloading carbon content is higher.

[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention and do not constitute a limitation on the content of the present invention. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a hydrocarbon steam reforming catalyst, characterized in that: include: (1) taking a certain amount of potassium feldspar and sepiolite in a potassium hydroxide aqueous solution, soaking them at a certain temperature for a certain period of time, settling them, removing impurities, and performing a first drying to obtain substance a; (2) mixing the substance a and a carrier auxiliary agent to obtain a carrier b; (3) dissolving lanthanum salt or cerium salt, cobalt salt, and adding a certain amount of nickel salt to prepare an impregnation solution c, placing the carrier b in the impregnation solution c for a certain period of time, and then performing a second drying and a first calcination to obtain a mixture d; The concentration of the impregnation solution c and the porosity of the carrier b satisfy the following relationship: C=C1 / C2, A=C×ґ / Ԑ, C1 is the cobalt ion concentration; C2 is the lanthanum ion or cerium ion concentration; A is the influence factor; ґ is the catalyst tortuosity factor; Ԑ is the carrier particle porosity; the numerical range of C is 0.3-5; the numerical range of ґ is 2.2-7; the numerical range of Ԑ is 1.6-2.2; the numerical range of A is 0.3-20; (4) A certain amount of ruthenium salt is prepared into an impregnation solution e, and the mixture d is placed in the impregnation solution e for a certain period of time, followed by a third drying and a second calcination to obtain a catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of potassium feldspar to sepiolite is 1:4-1:

8.

3. The preparation method according to claim 1, characterized in that: In step (1), the soaking time is 180-360 minutes.

4. The preparation method according to claim 1, characterized in that: In step (1), the soaking temperature is 200-250°C.

5. The preparation method according to claim 1, characterized in that: In step (2), the carrier auxiliary agent is at least one of polyethylene glycol, starch, and sucrose.

6. The preparation method according to claim 1, characterized in that: In step (3), the nickel salt is at least one of nickel nitrate, nickel acetate, and nickel oxalate, and the lanthanum salt or cerium salt is a soluble salt.

7. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the lanthanum salt or cerium salt: the cobalt salt: the nickel salt is 1:0.67:1-1:1.2:1.

2.

8. The preparation method according to claim 1, characterized in that: In step (3), the first roasting is to heat the second dried semi-finished product to 180-250°C at a rate of 1-4°C / min, roast at a constant temperature for 1-2 hours, and then heat it to 350-450°C at a rate of 1-4°C / min and roast at a constant temperature for 2-3 hours; in step (4), the second roasting is to heat the third dried semi-finished product to 180-200°C at a rate of 1-4°C / min, roast at a constant temperature for 1-2 hours, and then heat it to 400-550°C at a rate of 1-4°C / min and roast at a constant temperature for 2-3 hours.

9. The preparation method according to claim 1, characterized in that: In step (4), the ruthenium salt is a water-soluble salt.

10. A hydrocarbon steam reforming catalyst prepared by the preparation method according to any one of claims 1 to 9, wherein the catalyst active components are distributed in multiple layers along the radial direction of the carrier, the outermost active component of the core is ruthenium, the catalyst promoter is lanthanum oxide or cerium oxide, the active component of the middle shell layer is nickel oxide and cobalt oxide, and the core is nickel oxide; wherein, Ruthenium accounts for 0.02-0.2% of the catalyst mass, lanthanum oxide or cerium oxide accounts for 0.5-1.5% of the catalyst mass, nickel oxide accounts for 5.5-8.5% of the catalyst mass, cobalt oxide accounts for 1-3.8% of the catalyst mass, and the remaining components of the catalyst are composite carriers.

Citation Information

Patent Citations

  • Cobalt-cerium / sepiolite catalyst as well as preparation method and application thereof

    CN109847759A

  • Hydrocarbon steam pre-conversion catalyst and preparation method thereof

    CN110876936A

  • Steam reforming catalyst for hydrocarbons and method of producing the catalyst

    US4988661A

  • Hydrocarbon-cracking catalyst, method for producing hydrogen-containing mixed reformed gas using same, and fuel cell system

    WO2014021224A1